PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMPN 29 PADANG - Elpha, Fressa Pratiwi; Arief, Ermawati; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2019)
ABSTRACT The purpose f this research are (1) To know the students class VIII at SMPN 29 Padang ability to write eksplanation text without using cooperative learning type think pair share. (2) To know the students class VIII at SMPN 29 Padang ability to write explanation text using cooperative learning type think pair share. (3) To analyze the effects of using cooperative learning type think pair share towards students ability to write explanation text class VIII at SMPN 29 Padang. This is qualitative research using quasi experiment. Based on data analysis, using cooperative learning type think pair share affects to students class VIII SMPN 29 Padang ability to write explanation text. Kata kunci: Pengaruh, Model Pembelajaran Kooperatif Tipe Think Pair Share, Menulis Teks Eksplanasi